Reasons Behind Consumer's Behavioral Intentions Toward Digital Piracy - Abdul Aziz, Nor Azah; Khoo, Qiu Ti; Azman, Hartini; Sufian, Atirah (American Scientific Publishers, 2020)
This study investigates the reasons (social influence, economic factors, consumer morality and technology factors) that influence punter's behavioral intention toward digital piracy. The study adopted a quantitative method, and 150 questionnaires were distributed to target respondents In this research through Google Form Online. From the result, three factors showed a significantly positive relationship with consumer's behavioral intention toward digital piracy. This study can help related parties to more understand the reasons behind consumers' behavioral Intentions toward digital piracy and achieve reducing digital piracy case purposes.